Numerical modeling of micro single-chamber ceria-based SOFC - Chung, Chan-Yeup; Chung, Yong-Chae; Kim, Joosun; Lee, Jongho; Lee, Hae-Weon (SPRINGER, 2006)
Performance of intermediate temperature SOFC system of micro scale single-chamber with composite electrodes alternately placed on the ceria-based electrolyte has been successfully evaluated by numerical modeling. The polarization curve was obtained through a series of calculations for ohmic loss, activation loss and concentration loss. The calculation of each loss was based on the consideration of fluid dynamics, convection of fuel-air gas mixture, diffusion and oxygen ion conduction. The performance characteristics of SOFC were quantitatively investigated for various structural parameters such as distance between electrodes and thickness of electrolyte and electrode. The effect of the inflow direction of fuel-air mixture on the performance of the fuel cell was analyzed.
Keywords: OXIDE FUEL-CELL; PERFORMANCE; ELECTRODE